Analisis dimensi proses kognitif pada soal formatif dalam buku bahasa indonesia aku bisa kelas 1 sekolah dasar - Sayekti Uji Harini; Sukarno Sukarno; Siti Wahyuningsih (Universitas Sebelas Maret, 2023)
This study aims to describe and analyze the distribution of cognitive process dimensions in formative questions in the Indonesian language book